1990
DOI: 10.1149/1.2086652
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Electrochromic Amorphous  WO 3 Film in Lithium‐Salt Electrolyte

Abstract: The electrochromic behavior of amorphous WO3 films prepared by electron-beam deposition has been studied. SIMS analysis has revealed that lithium accumulates in amorphous WO3 films during reversible coloring and bleaching in propylene carbonate solution of LiC104. When a large quantity of lithium has been injected into WO3 films, an absorption spectrum different from tungsten bronze is observed. In these films, lithium tungstate has been observed using x-ray photoelectron spectroscopy and x-ray diffraction ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The enlarged d values of the oxides after the CV tests could be attributed to Li + ions being trapped (left behind) within the oxide lattice, which could not be detected using the TEM technique. It has been proposed that Li + inserted into the oxide lattice during the coloration process cannot be completely extracted during the detrapping process . It has been argued that the Li + would be located close to the W 5+ color centers, binding to the O coordination shells of W 5+ sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enlarged d values of the oxides after the CV tests could be attributed to Li + ions being trapped (left behind) within the oxide lattice, which could not be detected using the TEM technique. It has been proposed that Li + inserted into the oxide lattice during the coloration process cannot be completely extracted during the detrapping process . It has been argued that the Li + would be located close to the W 5+ color centers, binding to the O coordination shells of W 5+ sites.…”
Section: Resultsmentioning
confidence: 99%
“…The stability and degradation of electrochromic materials are essential issues affecting the ultimate performance of chromic devices; however, these issues have not been fully dealt with in the past and fundamental understanding remains a huge challenge. According to Hashimoto et al., the cause of degradation in WO x electrochromic devices is a result of Li + accumulation at the initial stage of coloring and bleaching cycles . Similar ion-trapping models were also proposed to explain the degradation of WO x thin films. , To study the electrochromic performance and understand the degradation behavior of the alkali-metal-intercalated WO x compounds, the fundamental insertion parameters of the alkali metal ions such as the diffusion coefficient need to be investigated to establish links with the detailed kinetic behavior of the intercalation compounds, because the processing parameters have a strong influence on the crystalline structures of the compounds.…”
Section: Introductionmentioning
confidence: 99%
“…We proposed that the electrochromism of the amorphous WO3 film is degraded by the formation of lithium tungstate, because an accumulation of lithium in the film was obtained after the coloring and bleaching cycles and a crystalline lithium tungstate was observed in the film after a large amount of lithium was injected (6). We found that the lifetime increases when WO3-TiO2 films are used as the electrochromic layer.…”
mentioning
confidence: 94%
“…It is evident that the lithium-ion trapping in the host structure would result in an electrode degradation by direct or indirect electrochemical redox in electroactive support electrolytes, giving rise to irreversible electrochemical reactions. [6][7][8][9][10] Generally accepted in situ or ex situ characterization techniques for probing the electrochemical degradation include electrochemical workstation, [11,12] X-ray diffraction, [13,14] optical spectroscopy, [15,16] Raman spectroscopy, [17] X-ray photoelectron spectroscopy, [18] and in situ transmission electron microscopy (TEM). [19,20] It is reported that tungsten trioxide (WO 3 ) shows a wide range of applications in the field of ECDs, [2] batteries, [21] capacitors, [22] photocatalysis, [23] and electrocatalytic environmental treatment, [24] owing to its reversible interfacial chemical and physical properties such as the reversible transformation from semiconductor (WO 3 ) to conductor (lithium tungsten bronze, Li x WO 3 ) in a Li + -based electrolyte.…”
mentioning
confidence: 99%